2017
DOI: 10.3390/su9101794
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Current Scoring Distribution by Evaluation Criteria in Korean Long-Life Housing Certification System Cases

Abstract: Peoples lifestyles are diversifying due to an increase in the types of residents housing and family structures. The ratio of apartment housing in Korea was 59.9% (9806 households) in 2015, and this type accounts for the largest ratio among all housing types. However, the life of the physical housing is approximately 30-40 years, which is relatively shorter in comparison to that of overseas houses. Therefore, the certification system for long-life housing, which had longer social and physical service life, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Figure 2 shows the main drivers and feedbacks The whole process started with interviewing farmers [4,57]. For these purposes, we applied the focus group interview method [58], which is well suited for a sample population with homogeneous characteristics [59]. Addressing the topic by the focus group interview method elicits the interaction and discussion, which strengthen the quality of generated responses [60,61].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the main drivers and feedbacks The whole process started with interviewing farmers [4,57]. For these purposes, we applied the focus group interview method [58], which is well suited for a sample population with homogeneous characteristics [59]. Addressing the topic by the focus group interview method elicits the interaction and discussion, which strengthen the quality of generated responses [60,61].…”
Section: Methodsmentioning
confidence: 99%
“…The above-mentioned implications (i.e., providing economic incentives) may also be applicable to other countries with regard to increasing the amount and share of sustainable housing. In particular, subsidies/tax deductions are important for promoting this type of housing in countries with short average house lifetimes (similar to Japan), such as Korea [ 21 ]. However, because characteristics (e.g., response to economic incentives), situations (e.g., economic situations), and policy systems (e.g., subsidies and taxes) differ by country, similar analyses are needed for other countries to further understand and confirm the factors that promote sustainable housing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Park and Tae [ 20 ] compared the housing policies of 10 countries on three aspects related to the quality of housing and offered policy suggestions to improve the quality of housing in Korea. Other studies include an evaluation of the scores and status of housing under the certification system for long-life housing in Korea [ 21 ], an evaluation of the lifecycle CO 2 emission reduction of long-life apartment housing in Korea [ 8 ], the development of regulations for Taiwan’s sustainable building (open building) [ 22 ], and a survey of stakeholders’ preferences for the “soft” features of sustainable and healthy housing in the UK [ 23 ]. In addition, a similar housing concept (e.g., sustainable housing) has also been studied from various perspectives, but the focus has been on design [ 24 , 25 ], affordability [ 26 , 27 ], community [ 28 , 29 ], urban construction [ 30 , 31 ], climate change mitigation [ 32 ], and energy savings and consumption [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minami (2016) argued that the concept of open building will play an important role in Japan's future [1]. Kim and Hwang (2017) indicated that long-life housing is a housing type in preparation for changes in residential environments in the future; long-life housing certification is evaluated in accordance with the total scores from the evaluation of each performance, as based on the durability, flexibility (the support and infill is evaluated for variability), and maintainability in Korea [14,15]. With the development of information technology and construction methods, combining open building concepts with building information modeling (BIM) techniques can be feasible to resolve the problems of sustainable renovation of old existing housing buildings [16,17].…”
Section: Open Building Theorymentioning
confidence: 99%